A non-native fish species reaches the south-western European waters: the Atlantic croaker, Micropogonias undulatus (Acanthuriformes, Sciaenidae) and its invasion history in Europe - de Carvalho-Souza, Gustavo; Gómez, Cristóbal; González-Ortegón, Enrique (Pensoft Publishers, 2024)
The Atlantic croaker Micropogonias undulatus , a sciaenid fish native to the North Atlantic American coast, holds importance in recreational and commercial fisheries. Moreover, its potential as an invasive species should be noted, given its expansion and establishment in Atlantic European waters. This study reports its southernmost occurrence in Europe, in the Gulf of Cadiz. Morphological and molecular analysis confirmed its identity, revealing genetic similarities to US sequences. A comprehensive review of historical non-native distribution records underscored the species' expansion throughout European waters, suggesting human-mediated introduction. The escalating frequency of such arrivals emphasises the critical need for effective monitoring and management efforts in order to control non-native species in this region.